Rupicolous habitats of interest for conservation in the central-southern Iberian peninsula - Piñar Fuentes, José Carlos (2017)
We studied the Quercus rotundifolia Lam. formations in the central-southern Iberian Peninsula, working particularly in areas in the Rondeño and Subbético biogeographical sectors. As a result we propose two new plant associations with an edaphoxeric character: Bupleuro gibraltarici-Quercetum rotundifoliae; and Junipero phoeniceae-Quercetum rotundifoliae included in habitat 9340. In both formations there is a high number of endemic plants often found in habitat 8210 "Calcareous rocky slopes with chasmophytic vegetation" like Antirrhinum graniticum, Antirrhinum onubense, Saxifraga reuteriana, Cerastium gibraltaricum.